The association between decision to delivery interval (DDI) and fetal outcome among patients with presumed fetal distress in Hospital Tengku Ampuan Afzan - Abdullah, Ainnun Ain (2022)
Background: In cases of emergency delivery, the fetus must be delivered in the shortest time possible. Guidelines in many countries have suggested keeping the decision delivery interval (DDI) to less than 30 minutes for such cases. However, many centres, especially in developing countries, cannot comply with the suggested interval, thus affecting the fetal outcome. Aim: To determine the DDI among patients who underwent emergency caesarean section for presumed fetal distress and its associated factors with fetal outcome. Materials and Methods: A retrospective study was conducted from January 2017 until June 2020. Medical records of 400 patients undergoing emergency caesarean section were reviewed and collated. The data was analysed using SPSS version 26 software. The DDI was described as mean with standard deviation in minutes. The association between DDI and fetal outcome was analysed using a chi-square test. Variables with a p-value of <0.05 were considered significant. Results: The mean DDI was 49.8 ± 12.01 minutes. Although there were higher percentages of adverse fetal outcomes among the DDI >30 minutes groups, the differences were statistically insignificant (p>0.05). Category of caesarean section, types of anaesthesia, longer transfer time and longer time for induction were significantly associated with longer DDI (p=0.022, 0.027, <0.001 and <0.001, respectively). Conclusions: The average DDI in our centre was longer than the recommended time. Although the DDI did not significantly affect the adverse fetal outcome, it should always be a significant contributing factor. Therefore, actions to shorten the DDI for emergency delivery must be considered